Genre-based approach to teaching English for Academic Purposes: Changes in undergraduates' academic writing - Ting, Su Hie; Law, Lily (Universiti Malaysia Sarawak, UNIMAS, 2008)
English for Academic Purpose (EAP) courses focus on developing undergraduates' language skills through explicit instruction on knowledge, skills and strategies needed to produce effective academic texts for various purposes at university. This study examined the changes in undergraduates' academic writing after taking an EAP course in terms of the structuring of the content and the use of language features relevant to the purpose of the text. Undergraduates enrolled in an EAP course were given a topic to write about at the beginning and at the end ofthe semester. The analysis of the write-up of24 undergraduates in a class indicated that there was preference for information reports although there were a fair number of explanation texts. The end-of-semester writing showed greater awareness of effective ways to structure a text to achieve the communicative purpose based on accepted conventions. There was evidence of improvement in the use of related language features and mechanics of writing, especially paragraphing. The impact of formal instruction in academic reading and writing on good and poor writers is discussed in relation to focal areas needing attention for better outcomes.